THE EFFECTIVENESS OF DIGITALIZATION IN VARIOUS SECTORS IN NEW UZBEKISTAN (International conference on multidisciplinary science, 2025)
The implementation of an e-government system and the development of a digital economy hold a strategic place in Uzbekistan's near-future development agenda. This primarily focuses on expanding the volume of electronic document exchange and gradually transitioning certain government services into digital formats via Public Service Centers. In this process, telecommunications infrastructure serves as a fundamental pillar, and its development plays a crucial role in the effective deployment of digital technologies. Today, we can observe that the economic, cultural, and other sectors of rapidly developing countries are increasingly based on digitalization. It is appropriate to regard this process as a defining feature of the 21st century. Therefore, comprehensive and practical efforts are being carried out in our country to advance and refine digitalization.